Development of a Critical Thinking Test Based on Higher-Order Thinking PISA Version: A Tool for Historical Learning in Senior High Schools - Alya Wulan Nur Fatimah; Nunuk Suryani; Sri Yamtinah (Centre for Behaviour and Wellness Advocacy, 2018)
Critical thinking assessment is vital in historical learning among Senior High School students. The purpose of this research was to develop a critical thinking test to evaluate the level of critical thinking in historical learning among Senior High School students. The development process of this test followed the Context, Input, Process, Product (CIPP) evaluation model by Daniel Stufflebeam. Validation of this instrument was done by experts and senior teachers in the field (practitioners). Though the total number of items in the test was 25, validity and reliability tests yielded 20 items. In conclusion, an assessment based on the higher order thinking Programme for International Student Assessment (PISA) version was as an adequate measure of critical thinking in historical learning at Senior High Schools.